Mniejszość niemiecka w Polsce a proces transformacji systemowej - założenia i wstępne wyniki badań - Mazurkiewicz, Marek (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The article presents the assumptions and partial results of the research undertaken within the project “German minority in Poland in the face of transition and political transformation after 1989”, carried out by a research team from the Institute of Political Science and Administration (University of Opole) and commissioned by the German Minority Research Center.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne